2019
DOI: 10.3390/ijms20215364
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Links between Central Obesity and Breast Cancer

Abstract: Worldwide, breast cancer (BC) is the most common malignancy in women, in regard to incidence and mortality. In recent years, the negative role of obesity during BC development and progression has been made abundantly clear in several studies. However, the distribution of body fat may be more important to analyze than the overall body weight. In our review of literature, we reported some key findings regarding the role of obesity in BC development, but focused more on central adiposity. Firstly, the adipose mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 161 publications
(149 reference statements)
0
54
0
1
Order By: Relevance
“…Several strong epidemiological and clinical studies support the correlation between mammary tumorigenesis, tumour progression and obesity. The main mechanisms underlying this link are capacity of conversion of androgenic precursors to estrogen through peripheral aromatization in adipose tissue, the alteration of physiological levels of insulin, insulin-like growth factor (IGF), adipokines, changes in the adipose tissue microenvironment and chronic lowgrade inflammation [33][34][35][36][37][38]. Juarez-Cruz JC et al [39] have recently shown that the leptin, a hormone secreted by adipocytes, through the FAK and Src kinases activation, contributes to BC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Several strong epidemiological and clinical studies support the correlation between mammary tumorigenesis, tumour progression and obesity. The main mechanisms underlying this link are capacity of conversion of androgenic precursors to estrogen through peripheral aromatization in adipose tissue, the alteration of physiological levels of insulin, insulin-like growth factor (IGF), adipokines, changes in the adipose tissue microenvironment and chronic lowgrade inflammation [33][34][35][36][37][38]. Juarez-Cruz JC et al [39] have recently shown that the leptin, a hormone secreted by adipocytes, through the FAK and Src kinases activation, contributes to BC progression.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that lower expression of LEPR (rather than higher expression as hypothesized) is an important indicator of more aggressive breast cancer, independent of race, BMI, and menopausal status, and might serve as an important biomarker associated with disparate outcomes, particularly among Black women. This seemingly counterintuitive observation is partially supported by data suggesting complex associations of obesity/adiposity, LEP/LEPR's activation of various signaling pathways, and breast cancer progression, which is further complicated by ER expression [46,47]. We hypothesize that central adiposity (rather than general obesity, as measured by BMI) is the etiologic mechanism linking LEPR expression in the breast tumor microenvironment with aggressive tumor clinicopathology and ultimately poorer prognosis.…”
Section: Discussionmentioning
confidence: 83%
“…Breast cancer is a heterogeneous disease with histopathology and molecular subtypes determining different clinical prognosis and risk factors [32]. Previous studies suggested that obesity may increase the risk of breast cancer [33]. Furthermore, BMI has been related to iron concentrations and breast cancer risk [34,35].…”
Section: Discussionmentioning
confidence: 99%